Analisis Faktor-Faktor yang Berhubungan dengan Tingkat Keparahan Dermatitis Atopik di Wilayah Kerja Puskesmas Kabila - Nazwa Salsabila Suma; Sirajuddien Bialan; Suardi (Jurnal Keperawatan Florence Nightingale, 2026)
Atopic dermatitis is a chronic inflammatory skin disease characterized by intense pruritus, recurrent exacerbations, and substantial impairment in quality of life. The persistently high number of atopic dermatitis cases within the Kabila Primary Health Center catchment area highlights the need to identify factors associated with disease severity. This study aimed to analyze factors associated with the severity of atopic dermatitis among patients in the Kabila Primary Health Center catchment area, Bone Bolango Regency. An analytical observational study with a cross-sectional design was conducted. The study population consisted of 181 adults diagnosed with atopic dermatitis, from which 125 respondents were selected using purposive sampling based on the Slovin formula. Data were collected using an atopic dermatitis knowledge questionnaire, the Food Frequency Questionnaire (FFQ) to assess dietary patterns, the stress subscale of the Depression Anxiety Stress Scale (DASS-42) to measure stress levels, a moisturizer-use questionnaire, and direct observation to assess atopic dermatitis severity. Data were analyzed using the Chi-square test with a 95% confidence level (α = 0.05).: Knowledge level was significantly associated with atopic dermatitis severity (p = 0.004). Dietary patterns were also significantly associated with disease severity (p = 0.001). In contrast, no significant associations were found between stress levels (p = 0.167) or moisturizer use (p = 0.300) and atopic dermatitis severity.  Knowledge level and dietary patterns were significantly associated with the severity of atopic dermatitis. Strengthening patient education and promoting appropriate dietary practices may contribute to improved disease control and reduced severity among individuals with atopic dermatitis.